2008
DOI: 10.1128/jvi.00641-08
|View full text |Cite
|
Sign up to set email alerts
|

Autophagosome Supports Coxsackievirus B3 Replication in Host Cells

Abstract: Recent studies suggest a possible takeover of host antimicrobial autophagy machinery by positive-stranded RNA viruses to facilitate their own replication. In the present study, we investigated the role of autophagy in coxsackievirus replication. Coxsackievirus B3 (CVB3), a picornavirus associated with viral myocarditis, causes pronounced intracellular membrane reorganization after infection. We demonstrate that CVB3 infection induces an increased number of double-membrane vesicles, accompanied by an increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
379
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(399 citation statements)
references
References 40 publications
(56 reference statements)
18
379
2
Order By: Relevance
“…Virus titer in the cell supernatant was measured using an agar overlay plaque assay as previously described. 50 In brief, the samples were serially diluted (10-fold) and overlaid onto a monolayer of HeLa cells. Following 1-h incubation, the medium was replaced with complete DMEM containing 0.75% agar.…”
Section: Methodsmentioning
confidence: 99%
“…Virus titer in the cell supernatant was measured using an agar overlay plaque assay as previously described. 50 In brief, the samples were serially diluted (10-fold) and overlaid onto a monolayer of HeLa cells. Following 1-h incubation, the medium was replaced with complete DMEM containing 0.75% agar.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, an increasing number of studies have demonstrated that the infection processes of morbilliviruses are closely related with autophagic flux [16,17]. However, the coxsackievirus B3, herpes simplex virus and influenza A virus have been shown to induce autophagosome formation but block the fusion of autophagosomes with lysosomes [4850]. More importantly, MeV infection induces successive autophagic signalling, leading to a sustained increase in autophagic flux [16].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown activation of autophagy pathways in several other viral infections, like influenza A virus, human immunodeficiency virus 1, hepatitis C virus, poliovirus, and coxsackievirus B3, supporting the importance of this evolutionarily conserved mechanism of stress adaptation in modulating viral replication efficiency by preserving the homeostasis of host cells (Wong et al. 2008; Zhou et al. 2009; Kim et al.…”
Section: Discussionmentioning
confidence: 99%